(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article deals with the implementation of the thermodynamic cycle using the two-component working fluid. An estimated calculation of the efficiency of using the two-component working fluid, and a variant implementation of the thermodynamic cycle rotary vane engine with an external heat supply are described.